THE IMPORTANCE OF ELEMENTS RELATED TO TABLES IN CREATING WEBSITES AND ELECTRONIC LEARNING RESOURCES (Journal of Science-Innovative Research in Uzbekistan, 2024)
this article highlights the importance of table elements in creating web pages and e-learning resources. When creating direct web pages, using the HTML language, table-related tags are important, with the help of which the general structure of the web page can be represented schematically. Also, in the process of presenting information on the web page, there is a need to use tables of various forms. In such cases, tables of the desired form can be achieved using HTML elements, especially table-related tags, their attributes and parameters.